IMPLEMENTASI DANA BANTUAN OPERASIONAL SEKOLAH (BOS) - Helnikusdita Helnikusdita Helnikusdita (UNIVERSITAS BENGKULU, 2016)
This study aims to describe the implementation of the use of school operational funds in SMA N 4 Seluma. The method used is descriptive qualitative research. Subjects were the principal, vice principal part of the infrastructure, BOS treasurer, teachers and committee. The conclusions of this research indicate that the implementation of school operational funds in SMA N 4 Seluma follow the procedures and rules that apply, the appropriate technical and operational guidelines BOS SMA.Keywords: operational assistance